MENDORONG BERPIKIR KREATIF MAHASISWA DALAM PEMBELAJARAN MATA KULIAH KAJIAN TEKS KURIKULUM KIMIA SMA - Izzatyl Zakiah (Lantanida Journal, 2014)
This study aims to determine student learning outcomes through the implementation of Learning Strategies Enhanced Thinking Skills (SPPKB) the text of the study subjects high school chemistry curriculum and student activities in developing chemical materials